2013
DOI: 10.1016/j.tcs.2012.10.045
|View full text |Cite
|
Sign up to set email alerts
|

On the polynomial depth of various sets of random strings

Abstract: This paper proposes new notions of polynomial depth (called monotone poly depth), based on a polynomial version of monotone Kolmogorov complexity. We show that monotone poly depth satisfies all desirable properties of depth notions i.e., both trivial and random sequences are not monotone poly deep, monotone poly depth satisfies the slow growth law i.e., no simple process can transform a non deep sequence into a deep one, and monotone poly deep sequences exist (unconditionally).We give two natural examples of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Several variants of logical depth have been studied in the past [2,9,16,18,21]. As shown in [21], all depth notions proposed so far can be interpreted in the compression framework which says a sequence is deep if given (arbitrarily) more than t(n) time steps, a compressor can compress the sequence r(n) more bits than if given at most t(n) time steps only. By considering different time bound families for t(n) (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several variants of logical depth have been studied in the past [2,9,16,18,21]. As shown in [21], all depth notions proposed so far can be interpreted in the compression framework which says a sequence is deep if given (arbitrarily) more than t(n) time steps, a compressor can compress the sequence r(n) more bits than if given at most t(n) time steps only. By considering different time bound families for t(n) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…and the magnitude of compression improvement r(n) -for short: the depth magnitude -(e.g. O(1), O(log n)) one can capture all existing depth notions [2,9,16,18,21] in the compression framework [21]. E.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…⊓ ⊔ As noticed in [15], for most depth notions it can be shown that easy and random sequences are not deep. The following two results show that this is also the case for deep (P,EXP) .…”
Section: Polynomial Depthmentioning
confidence: 92%
“…In this paper, we revisit their results [16] within the context of computational complexity theory. Adapting Bennett's logical depth to the computational complexity setting is an elusive task, and several authors have proposed polynomial versions of logical depth [2,7,15]; see [15] for a summary of most notions. Here we study a polynomial version of depth as close as possible to the original notion by Bennett, namely the difference of two Kolmogorov complexities with different time bounds.…”
Section: Introductionmentioning
confidence: 99%